Complex stress-strain behaviour of a cylindrical shell with a dynamically breaking internal elastic base - Antufiev Boris A. (Istrazivanja i projektovanja za privredu, 2020)
During the operation of a solid-propellant rocket engine, the combustion products of a powder charge create increased pressure in the combustion chamber. Besides, the combustion of gunpowder is accompanied by a large release of heat, which, despite the thermal insulation, causes the appearance of deformations in the engine cowling. This leads to the need to investigate the durability of the shell under the influence of internal pressure and temperature fields. The aim of the paper is to determine the complex dynamic deformed state and vibrations of the engine cowling under the action of force and temperature loads. The problem of a complex axisymmetric stress-strain state and vibrations of a thin cylindrical shell with a dynamically breaking internal elastic foundation, obeying Winkler's hypothesis, is approximately solved. The shell is under the action of internal pressure and temperature fields on a part of its length free from an elastic base. The resolving equation of the problem of the shell deflection is solved by the Bubnov-Galerkin method, reducing the problem to a system of linear algebraic equations. The examples are considered, in which the basic frequencies of natural vibrations of the structure are determined depending on the conditions of shell fastening. Parametric studies are carried out.